Analysis of the Mathematical Representation Ability of Class VIII Students in terms of Self Regulated Learning with the Inductive Discovery Learning Model - Putri, Arbai Syahidarahma; Veronica, Rahayu Budhiati (Unnes Journal of Mathematics Education, 2021)
The aim of this study was to determine the mathematical representation ability of class VIII students in terms of self regulated learning with the Inductive Discovery Leraning Model. This type of research is a mix methods research with a concurrent embedded desaign (unbalanced mix). The population in this study were class VIII students of SMP Negeri 40 Semarang in the academic year 2020/2021. The data collection technique used triangulation, comparing the data obtained from interviews, obsservations, and final tests of mathematical representation abilities. The research subjects selected were 6 students, consisting of 2 students with high self regulated learning, 2 students with medium self regulated learning, and 2 students with low self regulated learning. The results of the study indicate that students with high self regulated learning have high mathematical representation abilities, students with medium self regulated learning have medium mathematical representation abilities, and students with low self regulated learning have low mathematical representation abilities.